PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS IV PADA PEMBELAJARAN IPAS DI UPT SPF SDN 101826 TUNTUNGAN - Rani Wijaya Siringoringo; Anton Sitepu; Patri Janson Silaban; Nova Florentina Ambarwati; Jhonas Dongoran (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Picture and Picture type cooperative learning model assisted by Wordwall media on student learning outcomes in the subject of IPA class IV at UPT SPF SDN 101826 Tuntungan in the 2024/2025 Academic Year. The background of this study is based on the low learning outcomes of students caused by the use of conventional learning methods that do not involve student activity. The method used is quantitative research with a one group pretest-posttest design. The sample in this study was 26 fourth grade students. The information collection technique was carried out through tests and questionnaires. The results of the analysis showed that there was a significant increase in student learning outcomes after the application of the Picture and Picture cooperative model assisted by Wordwall. This is evidenced by the average posttest score of 83.58 which is higher with a very good category compared to the pretest of 51.84 with a less category. It can be said that the level of success of student learning outcomes has increased with the results of the correlation coefficient test calculation obtained r_count ≥r_tabel with a result of 0.875≥ 0.388. then hypothesis testing compares the value of obtained the t_count ≥t table with results of 8.857 while t_table = 1.706 because Because t_count ≥t_table (8.857 ≥ 1.706) then H_a is accepted and H_o is rejected. Through the t-test it can be concluded that there is a significant positive influence between the cooperative learning model of the picture and picture type assisted by wordwall media (X) on student learning outcomes (Y).